Development of Teaching Materials for Booklets on the Dynamics of Planet Earth As a Living Space in the Class X Merdeka Curriculum at SMAN 1 Mandastana - Puspita, Dea; Alviawati, Eva; Adyatma, Sidharta (Universitas Lambung Mangkurat, 2024)
The research is motivated by LKPD (Learner Worksheet) teaching materials used in monotonous schools that some students need help understanding, especially in the material on the dynamics of planet Earth as a living space. The research aims to produce a development product in the form of a booklet on the material of the dynamics of planet Earth as a living space to produce a booklet that is feasible and practical to use. The research method used is Research and Development (R&D) with the 4D model developed by Thiagarajan, namely Define, Design, Develop, and Disseminate, but in this study, it was modified only until the Develop stage. The study used quantitative data based on the validator's assessment questionnaire score and qualitative data based on criticisms and suggestions from validators regarding the teaching materials developed. The results of the research are in the form of booklet development products on the dynamics of planet Earth as a living space with the results of material feasibility 78%, linguistic feasibility 78.03%, and design feasibility 80% so that the booklet is declared feasible with a percentage of feasibility 78.03% and declared very practical with a percentage of practicality 85.52%.